Newborn screening for X-linked adrenoleukodystrophy in Italy: Diagnostic algorithm and disease monitoring - Bonaventura, Eleonora; Alberti, Luisella; Lucchi, Simona; Cappelletti, Laura; Fazzone, Salvatore; Cattaneo, Elisa; Bellini, Matteo; Izzo, Giana; Parazzini, Cecilia; Bosetti, Alessandra; Di Profio, Elisabetta; Fiore, Giulia; et al. (Frontiers in Neurology, 2023)
Introduction: X-linked adrenoleukodystrophy (X-ALD) is the most common inherited peroxisomal disorder, caused by variants in the ABCD1 gene. The main phenotypes observed in males with X-ALD are primary adrenal insufficiency, adrenomyeloneuropathy and cerebral ALD (cALD). cALD consists in a demyelinating progressive cerebral white matter (WM) disease associated with rapid clinical declining and, if left untreated, is fatal. Hematopoietic stem cell transplantation is the standard treatment for cALD as it stabilizes WM degeneration when performed early in the disease. For this reason, early diagnosis is crucially important, and several countries have already implemented their newborn screening program (NBS) with the assessment of C26:0-lysophosphatidylcoline (C26:0-LPC) values as screening for X-ALD. Methods: in June 2021, an Italian group, in Lombardy, launched a pilot study for the implementation of X-ALD in the Italian NBS program. A three-tiered approach is adopted, and it involves quantifying the values of C26:0-LPC and other metabolites in dried blood spot with FIA-MS/MS first, with the more specific ultra-performance liquid chromatography-tandem mass spectrometry (UHPLC-MS/MS) technique then, and finally the genetic confirmation via focused NGS. Discussion: genetically confirmed patients undergo a follow-up protocol and are periodically evaluated to promptly start a specific treatment if, and when, first signs of brain damage appear, as suggested by international guidelines. A specific disease monitoring protocol has been created based on literature data and personal direct experience Conclusion: the primary aim of this study is to develop a model able to improve the early diagnosis and subsequent follow-up and timely treatment of X-ALD. Ethics: the study was approved by the local Ethics Committee. The research is conducted in the absence of any commercial or financial relationships that could be construed as a potential conflict of interest